2017
DOI: 10.1080/16000889.2017.1299672
|View full text |Cite
|
Sign up to set email alerts
|

Source appointment of nitrogen in PM<sub>2.5</sub> based on bulk δ<sup>15</sup>N signatures and a Bayesian isotope mixing model

Abstract: 2017) Source appointment of nitrogen in PM 2.5 based on bulk δ 15 N signatures and a Bayesian isotope mixing model, Tellus B:ABSTRACT Nitrogen isotope (δ 15 N) has been employed to differentiate major sources of atmospheric N. However, it remains a challenge to quantify contributions of multiple sources based on δ 15 N values of the N mixture in atmospheric samples. This study measured δ 15 N of bulk N in PM 2.5 at an urban site of Beijing during a severe haze episode of 22-30 January 2013 and a background sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 66 publications
(84 reference statements)
2
11
0
Order By: Relevance
“…Sampling during summertime, oxidation of NO 2 through OH was expected to be the dominant pathway of nitrate formation, in accordance with observations from the subtropics (Hastings et al, 2003). However, our results highlight that N 2 O 5 hydrolysis can be an almost equally important process as the oxidization of NO 2 with OH with regards to the NO − 3 formation in cloud water (Wang et al, 2017b).…”
Section: Isotope-based Assessment Of the Sources And Formation Of Nitsupporting
confidence: 90%
“…Sampling during summertime, oxidation of NO 2 through OH was expected to be the dominant pathway of nitrate formation, in accordance with observations from the subtropics (Hastings et al, 2003). However, our results highlight that N 2 O 5 hydrolysis can be an almost equally important process as the oxidization of NO 2 with OH with regards to the NO − 3 formation in cloud water (Wang et al, 2017b).…”
Section: Isotope-based Assessment Of the Sources And Formation Of Nitsupporting
confidence: 90%
“…Moreover, there was no significant correlation between moss δ 15 N and NH 4 + /NO 3 − when using all the data (Figure 3(g) More positive δ 15 N values were observed in urban mosses in the YRD (−3.41‰ to −1.58‰), which is similar to that of urban Changsha in China (−6.75‰ to 1.94‰) (Xiao et al 2010b) and the center of the Ferrara municipality in Italy (−5.27‰ to 1.62‰) (Gerdol et al 2002). Many previous monitoring-based studies have indicated that the main source of atmospheric N deposition is fossil fuel combustion and vehicle emissions in urban areas (Wang et al 2017). Furthermore, Pearson et al (2000) found a very good correlation between moss δ 15 N and traffic exposure, where the average δ 15 N of moss near busy urban roads is +3.66‰ (−1‰ to +6‰).…”
Section: Moss δ 15 N For Indicating Main Sources Of Atmospheric N Depsupporting
confidence: 70%
“…For instance, the sum contributions of several sources to one or several components measured in a sample or some samples collected for a period of time can be defined as a value or range. Once developed, this will provide a powerful tool for using PMF to apportion PM 2.5 to sources, because knowledge on the sources of not only carbon-containing matter but also nitrogen- and sulfur-containing matter, in PM 2.5 determined by their respective stable isotope measurements can be considered a priori information to constrain PMF models 10 12 , 24 , 25 . Nitrogen-, sulfur-, and carbon-containing matter account for the majority of PM 2.5 mass concentrations 18 , 26 .…”
Section: Resultsmentioning
confidence: 99%